Phytochemicals and bioactivities of cinnamomum porrectum (Roxb.) kosterm and cinnamomum mollissimum hook F - Masnon, Fatin Fasihah (2014)
Cinnamomum porrectum (Roxb.) Kosterm and Cinnamomum mollissimum Hook f. which belong to the Lauraceae family are widely distributed in Peninsular Malaysia. They are locally known as “medang kemangi” and “medang lawang”, respectively. The leaves and barks of C. porrectum and the leaves of C. mollissimum were extracted by cold extraction using methanol and the extracts were then partitioned using different solvents with increasing polarity to yield the petroleum ether, chloroform and ethyl acetate extracts. Acidification, basification and extraction of the methanol extract from the barks of C. mollissimum with chloroform produced the neutral and alkaloid crude extracts. The isolation and purification on the crude extracts were achieved using chromatographic techniques and have resulted in the isolation of prenylpropanoid, triterpenes, ester, carboxylic acid and aporphine alkaloids. Structure of the isolated compounds were elucidated using spectroscopic techniques including infrared, ultraviolet-visible, nuclear magnetic resonance spectroscopies, mass spectrometry and also by comparison of the spectral data with those previously reported in the literatures. Purification process of the leaves extracts of C. porrectum have yielded three compounds identified as methyl eugenol, ß-sitosterol and stigmast-4-en-3-one. Benzyl benzoate and benzoic acid have been isolated from the leaves of C. mollissimum. Purification of the alkaloid extract from the barks of C. mollissimum produced five aporphines, namely isocorydine, N-methylhernagine, N-methylhernovine, hernagine and hernovine. Several bioactivities such as antibacterial, antioxidant and antityrosinase have been investigated for the crude extracts and selected compounds. The antibacterial assays were performed using disc diffusion method, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The results showed that the alkaloid extract, methyl eugenol and benzyl benzoate exhibited strong antibacterial activity towards selective bacterial strains with the concentration ranged less than 500 µg/mL. The antioxidant activity by DPPH showed significance results on the alkaloid extract and hernovine with SC50 50.1 µg/mL and 50 µg/mL, respectively. The crude extracts which were screened for antityrosinase activity using mushroom tyrosinase were found to be inactive with IC50 > 1000 µg/mL. As a conclusion, the alkaloid extract showed good activity towards all the tested bioassays except for the tyrosinase inhibition assay. The activity portrayed was due to the synergistic effect between the compounds presence in the extract.